Political interference and crowding out in bank lending - Kumar, Nitish (Journal of Financial Intermediation, 2020)
I provide novel evidence on the real costs of political interference in bank lending. Analyzing staggered state elections in India, I show that politically motivated increased bank lending to farmers before elections crowds out lending to manufacturing firms. These lending distortions are larger where farmers have more political weight and where incumbents have more influence over banks. Reduced bank credit forces manufacturing firms to cut production and operate at lower factor utilization. I also provide evidence suggesting politically motivated increased agricultural lending before state elections contributed towards excessive indebtedness of farmers and a subsequent costly bailout in 2008.